Performance Evaluation of Overcurrent Relay Coordination on 20-kV Busbar and Feeders - Ageng Rizkianto; Agung Trihasto; Deria Pravitasari; Hery Teguh Setiawan (Institut Teknologi Dirgantara Adisutjipto, 2026)
The coordination of Overcurrent Relays (OCR) in power systems is crucial to ensure selectivity and reliability. Mis-coordination between OCRs on the 20-kV busbar and feeders can significantly reduce system performance, often due to improper determination of pick-up values and Time Multiplier Setting (TMS). Previous studies mostly focused on protection coordination for a single feeder and relied solely on simulation. This study evaluates OCR coordination on the 20-kV busbar and five feeders connected to the Unit I transformer at Secang Substation by combining manual analysis and Electrical Transient Analyzer Program (ETAP) simulations, validated against IEEE Std 242-2001. This integrated approach provides more reliable insights than earlier works limited to single-feeder coordination or software-only methods. Evaluation was conducted through short-circuit current analysis and Time Current Characteristic (TCC) curves, yielding pick-up and TMS values that produce Coordination Time Intervals (CTI) in compliance with IEEE Std 242-2001. Results indicate that the busbar OCR achieved a pick-up of 0.566 and a TMS of 0.236. For the feeders, SCG 10 achieved 0.27 and 0.173; SCG 03 yielded 0.5025 and 0.147; SCG 05 produced 0.441 and 0.153; SCG 07 yielded 0.35 and 0.165; and SCG 08 achieved 0.5535 and 0.137. Applying these settings produced CTI values exceeding the minimum requirement of 0.3 seconds. This evaluation demonstrates that coordinated OCR settings can improve reliability in 20-kV distribution systems and reduce the risk of widespread outages due to protection failures.